Coming to Accounts: Fraud and Muckraking in Charles W. Chesnutt’s The Marrow of Tradition - Mark David Kaufman (European Journal of American Studies)
This article traces the rhetoric of accounting in nineteenth-century and early twentieth-century racial discourse, from its initial use by slave traders, to its reinscription (or re-metaphorization) as “fraud” by abolitionists, and finally to its turn-of-the-century valence in exposing the linguistic double-dealing and metonymic substitution that informed—and continues to inform—racist ideology.With its emphasis on bodysnatching, doubling, and displacement of “figures,” Charles W. Chesnutt’s 1901 novel The Marrow of Tradition exposes the fallacious logic, the traces of the trade, which persisted in the figuration of racial relations in post-Reconstruction America. In doing so, Chesnutt’s novel participates in, or prefigures, a method of journalistic “muckraking” that was soon to characterize the first decade of the twentieth century.